Exploration of Project-Based Learning in Islamic Religious Education in Elementary Schools - Nelfa Sari; Rini Putri Handayani (Ahlussunnah: Journal of Islamic Education, 2025)
This study aims to explore the planning and implementation of Islamic Religious Education learning based on Project Based Learning (PjBL). The research employs a qualitative approach with a case study design to gain an in-depth understanding of the phenomenon. The subjects consist of Islamic Religious Education teachers, school principals, and students from grades four and five, serving as the primary and secondary data sources. Data collection techniques include observation, interviews, and documentation to ensure comprehensive and triangulated data. Data analysis is conducted through data reduction, data display, and drawing conclusions to provide a thorough interpretation of the findings. Prior to the learning process, the teacher prepares detailed lesson plans and learning devices to guide the implementation. The Project-based learning (PjBL) steps consist of project orientation, group division, project planning, implementation, presentation, and reflection, which are systematically carried out to foster active student engagement. This method encourages students to work collaboratively, develop creativity, and apply their knowledge in producing real projects. The findings of this study offer valuable insights into effective strategies for planning and implementing Project-based learning (PjBL) in Islamic Religious Education, emphasizing the importance of systematic preparation, teacher facilitation, and active student participation. The study highlights that when well-planned and executed, Project-based learning (PjBL) can enhance the quality of learning by making it more meaningful and relevant to students’ lives.